The logic in academic research - Casillas-Llerena, Pedro J. (2021)
All research work has a reasoning process. This process begins with the most elementary logic of our human nature. But then this reasoning deepens when we turn to logic as a discipline. Whoever is in charge of imparting this knowledge to us is a logic teacher, who, in addition to knowing logic, must know how to transmit his knowledge, must teach with logic. This happens in a similar way with a teacher of any subject, discipline or skill. Any teacher must teach with logic. Teaching with logic is teaching with coherence in the context of demonstration, contrast, or verification. Teaching with logic is showing that all research has an explanatory sequence; it is to give reasons, foundations about an idea that is being defended. In the world of academic research, a thesis involves a demonstration process, which is born in the same research project. The process of building a thesis project implies a strictly logical background.